2004
DOI: 10.1002/ange.200353473
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ‐Erzeugung hochaktiver gelöster Pd‐Spezies aus Feststoffkatalysatoren – ein Konzept zur Aktivierung von Chlorarenen in der Heck‐Reaktion

Abstract: Optimierte Pd/Metalloxid‐Systeme sind hochaktive heterogene Katalysatoren für Heck‐Reaktionen. Nichtaktivierte und desaktivierte Chlorarene können schnell an Pd/Zeolith(NaY)‐Katalysatoren umgesetzt werden (siehe Gleichung). Bei diesen Reaktionen sind die Ablösung des Palladiums von der Trägeroberfläche und dessen Wiederabscheidung sowie die Steuerung dieser Gleichgewichte entscheidend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Higher conversions were also observed in irradiated reactions (81.7%) than in unirradiated reactions (61.4%) using Pd(II)/Al 2 O 3 . With heterogeneous catalysts, solubility factors such as Pd leaching play a significant role in conversion [21,[23][24][25][26]. Therefore, this may overshadow some of the effect light has on the reaction, especially in the case of Pd(II)/Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Higher conversions were also observed in irradiated reactions (81.7%) than in unirradiated reactions (61.4%) using Pd(II)/Al 2 O 3 . With heterogeneous catalysts, solubility factors such as Pd leaching play a significant role in conversion [21,[23][24][25][26]. Therefore, this may overshadow some of the effect light has on the reaction, especially in the case of Pd(II)/Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[75][76][77][78][79] Among them the zeolites showed exceptional activity and stability. [62,69,70,73] Most of the work reported in this area concerned mainly model reactions, reacting aryl iodides and bromides with styrene or acrylates. Few reports concern the reaction of aryl chlorides with styrene.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports concern the reaction of aryl chlorides with styrene. [69,70] As a part of our studies in developing synthetic methods for fine chemical synthesis, we decided to evaluate several palladium catalytic systems for the arylation of acrolein diethyl acetal, especially, heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Both heterogeneous and homogeneous catalysts were used for Suzuki reactions and showed remarkable activities. The best known heterogeneous catalysts are metal oxides, [11][12][13] supported catalysts on zeolites/silica/coal [14][15][16][17][18][19] or polymer resins. [20][21][22][23][24][25][26] Among the homogeneous catalysts, a huge number of different ligands can be found that address different problems.…”
Section: Introductionmentioning
confidence: 99%
“…1 H and 13 C NMR spectra were recorded on a Jeol ECX-400 400 MHz spectrometer at ambient temperature. Boronic acids and aryl bromides were purchased from Acros Organics and used without further purification.…”
mentioning
confidence: 99%